2015
DOI: 10.1097/ico.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Vision-Related Quality-of-Life Assessment Using NEI VFQ-25 in Patients After Boston Keratoprosthesis Implantation

Abstract: The quality of life of patients who underwent KPro significantly improved postoperatively compared with their preoperative status. These results did not change when stratifying by visual acuity of the contralateral eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…These findings suggest that KPro implantation improves visual acuity and the patient’s participation in daily tasks, and vision-specific emotional well-being—despite the relatively intensive follow-up management required especially early postsurgery. Our study was consistent with a previous report of a mean significant improvement in the overall score of the NEI-VFQ-25 in a similar clinical sample of patients undergoing KPro surgery 6. However, our study was able to analyse the impact of KPro on subscales such as reading and accessing information, mobility and independence; and emotional well-being scores.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings suggest that KPro implantation improves visual acuity and the patient’s participation in daily tasks, and vision-specific emotional well-being—despite the relatively intensive follow-up management required especially early postsurgery. Our study was consistent with a previous report of a mean significant improvement in the overall score of the NEI-VFQ-25 in a similar clinical sample of patients undergoing KPro surgery 6. However, our study was able to analyse the impact of KPro on subscales such as reading and accessing information, mobility and independence; and emotional well-being scores.…”
Section: Discussionsupporting
confidence: 92%
“…As most patients in our study suffered from end-stage corneal disease with poor vision in both eyes, our study suggests that the benefit of KPro implantation extends beyond improvement in visual acuity. This observation is similar to the only other study on VRQoL in patients with KPro,6 where despite a relatively low BCVA, patients report a great improvement in VRQoL, suggesting that the perceived benefit may be larger than what is estimated by outcome measures such as vision. In support of this observation, we also found that the changes in BCVA postoperatively were not significantly associated with changes in VRQoL scores, that is, BCVA only explained a low percentage of the variance in VRQoL outcomes in our multivariate analysis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“… 10 , 11 A recent study evaluated patient responses to the National Eye Institute Visual Function Questionnaire 25 (NEI VFQ-25) following Kpro implantation, and found a significant improvement in quality-of-life measures even in those patients with vision better than 20/200 in their nonsurgical eye. 12 To optimize outcomes, patients should possess certain essential characteristics, including adequate lid anatomy, good blink function, controlled ocular surface inflammation, and a sufficiently moist ocular surface.…”
Section: Preoperative Evaluationmentioning
confidence: 99%